2008
DOI: 10.1007/s10633-007-9111-8
|View full text |Cite
|
Sign up to set email alerts
|

VEP maturation and visual acuity in infants and preschool children

Abstract: These findings indicate the expected maturation of flash, reversal and onset VEPs, and demonstrate their correlation to normal development of visual acuity. Maturation of VEP latencies is associated with development of visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 29 publications
3
40
0
1
Order By: Relevance
“…This may explain why significant differences were found in pattern-reversal VEPs and not in flash VEPs. Sweep VEPs are likely the best way to test cortical responses in infants, because they take the shortest time to elicit and there would be less chance of a child loosing attention to the stimulus [4244]. The authors reported VEP results using latencies which are less variable than amplitudes [44].…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why significant differences were found in pattern-reversal VEPs and not in flash VEPs. Sweep VEPs are likely the best way to test cortical responses in infants, because they take the shortest time to elicit and there would be less chance of a child loosing attention to the stimulus [4244]. The authors reported VEP results using latencies which are less variable than amplitudes [44].…”
Section: Discussionmentioning
confidence: 99%
“…It is of established value in the assessment of optic nerve, chiasmal and retrochiasmal function [8][9][10]. Normal values are age-dependent, with increasing peak time in the elderly and rapid maturation of the VEP during infancy [11]. Multiple posterior recording electrodes allow interhemispheric comparison; asymmetrical distribution of VEPs across the occipital areas may indicate chiasmal or retrochiasmal dysfunction that cannot be detected using only a midline recording.…”
Section: The Basics Of Electrophysiological Testingmentioning
confidence: 99%
“…According to age, P1 and N1 implicit time peaks and P1N1 duration increased with age, similar to normal flash and pattern reversal VEP (20)(21)(22)(23)(24)(25) . We also observed that P1 amplitude in the right eye increased with age, but this finding should be considered with caution because, although this variable has reached statistical significance, the Pearson's correlation coefficient suggests a weak association.…”
Section: Discussionmentioning
confidence: 59%